Plant miRNA integrated functions in development and reproduction - Arnaud, Nicolas; Laufs, Patrick (Frontiers in Plant Physiology, 2023)
Plant development and reproduction are complex processes during which an individual fulfills its life cycle, starting from germination and the elaboration of new organs and growth, leading to the formation of reproductive structures and ultimately terminating in the production of the next generation. These mechanisms are the result of a long evolutionary history that has led to sophisticated regulatory mechanisms involving multiple levels of regulators. MicroRNAs (miRNAs) are a class of small regulatory molecules that play a pivotal role in regulatory networks by negatively controlling target genes. Since miRNA very first identification twenty years ago, they have attracted much interest for their role as essential regulators of plant development. In this review, we propose a comprehensive and critical analysis of the importance of miRNAs during plant development and reproduction. We begin by presenting the current understanding of miRNAs’ evolutionary history, biogenesis, mode of action, position in regulatory networks, and their potential as mobile molecules, exploring how these aspects contribute to their functions in plant development and reproduction. Then, we explore the genetic strategies employed to effectively analyze their roles, with an emphasis on recent advancements resulting from genome editing techniques. Next, we focus on miRNA contributions to four crucial processes: growth, organ patterning and identity, life cycle progression and reproduction. Through this analysis, the importance of miRNAs during plant development and reproduction emerges, which we finally discuss in light of the current view miRNAs’ roles during animal development.